Transient Heat Transfer - Annaratone, Donatello (SpringerBriefs in Applied Sciences and Technology, 2011)
This book presents a new and direct computational method for transient heat transfer. The approach uses the well-known dimensionless Biot number and a second dimensionless number introduced by the author. The methodology allows for a transient heat transfer calculations without using finite difference programs. The book presents many examples and various tables demonstrating the potential of this new methodology. Many diagrams illustrate the physical phenomena.